Surface‐Engineered Monocyte Inhibits Atherosclerotic Plaque Destabilization via Graphene Quantum Dot‐Mediated MicroRNA Delivery. Issue 15 (6th June 2019) - Liu, Feila; Ding, Ning; Huo, Da; Yang, Guanyuan; Wei, Keyu; Guan, Ge; Li, Yanzhao; Yang, Jingyuan; Wang, Tianran; Wang, Yeqin; Tan, Ju; Zeng, Wen; et al.
Abstract: Rupture‐prone atherosclerotic plaque is the cause of the high mortality and morbidity rates that accompany atherosclerosis‐associated diseases. MicroRNAs can regulate the expression of a variety of atherosclerotic inflammation‐related genes in macrophages. There are currently no definitive methods for delivering microRNAs into the interior of plaque. Monocytes typically possess a pathological feature that allows them to be recruited to atherosclerotic plaque resulting in rupture‐prone; however, whether monocytes can be modified to be gene carriers remains unclear. In this study, a novel monocyte surface‐engineered gene‐delivery system based on graphene quantum dots (GQDs) is developed. Briefly, GQDs‐microRNA223 linked by disulfide bonds are grafted onto the monocyte membrane via a carefully designed C18‐peptide (C18P) containing a hydrophobic end to afford the designed monocyte‐C18P‐GQDs‐miR223 architecture. The system can reach and enter the interior of the plaque and release the GQDs‐miRNA via C18P digestion. The released GQDs‐miRNA are taken up by the macrophages in atherosclerotic plaques, and the disulfide linkages between the GQDs and the miRNA are cleaved through γ‐interferon‐inducible lysosomal thiol reductase (GILT) in the lysosome. Under the protection of GQDs, miRNA cargos are transfected into the cytosol and subsequently undergo nuclear translocation, allowing a significantly reduced plaque burden by regulating inflammatory response in vivo. Abstract : GQDs‐miR223 linked by disulfide bonds is grafted onto the monocyte membrane via a carefully designed C18‐peptide containing a hydrophobic end to afford the architecture of monocyte‐C18P‐GQDs‐miR223. This novel monocyte surface‐engineered gene‐delivery system is constructed for transporting, targeting and releasing of gene species into macrophages of atherosclerotic plaque, allowing a significantly reduced plaque burden by regulating inflammatory response in vivo.